A note on discrete maximal regularity for functional difference equations with infinite delay - Cuevas Claudio; vidal Claudio (Advances in Difference Equations, 2006)
Using exponential dichotomies, we get maximal regularity for retarded functional difference equations. Applications on Volterra difference equations with infinite delay are shown.